The Effectiveness of ROR in Reading Comprehension of Narrative Text - Agustina Nababan; Dewi Yana; Sri Sugiharti (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The objective of this research was to know the effectiveness of Rank Ordering Retell Strategy on reading comprehension of the eight grade students’ of SMP Advent Batam in academic year 2015/2016. The method was used in this research is experimental research, the research focused on True experimental Design. The population in this research was all students of eight grade students at SMP Advent Batam in academic year 2015/2016. The number of the entire students is 163. The researcher used cluster random sampling technique to determine class of the research. The subject of the study was the grade VIII – 2 and VIII – 3. There were 32 students each class. The researcher conducted research in two classes. The first class (VIII – 2) was as experiment class and the second class (VIII – 3) as control class. The experiment class was taught reading narrative text using Rank Ordering Retell Strategy, while control class was taught reading narrative text using conventional strategy (lecture method). In analyzing the data, the researcher used a quantitative measurement to find the result. The analysis of the data showed that there was a significant difference of the students’ achievement before conducted treatment the average of the students’ was 62.34 for experimental class and 64.22 for control class. While the average of the students’ achievement after conducted treatment in experimental class was 79.38 and in control class was 68.75. Based on this finding, it can be concluded that the used of Rank Ordering Retell Strategy gave significant effect in reading comprehension than the use of conventional strategy (lecture method).Keywords: rank ordering retell strategy, reading comprehension, narrative text.